A multicenter randomized phase 4 trial comparing sodium picosulphate plus magnesium citrate vs. polyethylene glycol plus ascorbic acid for bowel preparation before colonoscopy. The PRECOL trial - Valentina D’Angelo; Maria Carmela Piccirillo; Massimo Di Maio; Ciro Gallo; Cristina Bucci; Corrado Civiletti; Elena Di Girolamo; Pietro Marone; Giovanni Battista Rossi; Alfonso Mario Tempesta; Maura C. Tracey; Marco Romano; et al. (Frontiers in Medicine, 2022)
BackgroundAdequate bowel preparation before colonoscopy is crucial. Unfortunately, 25% of colonoscopies have inadequate bowel cleansing. From a patient perspective, bowel preparation is the main obstacle to colonoscopy. Several low-volume bowel preparations have been formulated to provide more tolerable purgative solutions without loss of efficacy.ObjectivesInvestigate efficacy, safety, and tolerability of Sodium Picosulphate plus Magnesium Citrate (SPMC) vs. Polyethylene Glycol plus Ascorbic Acid (PEG-ASC) solutions in patients undergoing diagnostic colonoscopy.Materials and methodsIn this phase 4, randomized, multicenter, two-arm trial, adult outpatients received either SPMC or PEG-ASC for bowel preparation before colonoscopy. The primary aims were quality of bowel cleansing (primary endpoint scored according to Boston Bowel Preparation Scale) and patient acceptance (measured with six visual analogue scales). The study was open for treatment assignment and blinded for primary endpoint assessment. This was done independently with videotaped colonoscopies reviewed by two endoscopists unaware of study arms. A sample size of 525 patients was calculated to recognize a difference of 10% in the proportion of successes between the arms with a two-sided alpha error of 0.05 and 90% statistical power.ResultsOverall 550 subjects (279 assigned to PEG-ASC and 271 assigned to SPMC) represented the analysis population. There was no statistically significant difference in success rate according to BBPS: 94.4% with PEG-ASC and 95.7% with SPMC (P = 0.49). Acceptance and willing to repeat colonoscopy were significantly better for SPMC with all the scales. Compliance was less than full in 6.6 and 9.9% of cases with PEG-ASC and SPMC, respectively (P = 0.17). Nausea and meteorism were significantly more bothersome with PEG-ASC than SPMC. There were no serious adverse events in either group.ConclusionSPMC and PEG-ASC are not different in terms of efficacy, but SPMC is better tolerated than PEG-ASC. SPMC could be an alternative to low-volume PEG based purgative solutions for bowel preparation.Clinical trial registration[ClinicalTrials.gov], Identifier [NCT01649674 and EudraCT 2011–000587–10].